ceRNA regulatory network and immune-neurodegenerative mechanisms of peripheral CD4+ T cells in parkinson’s disease - Guo, Lijun; Li, Qiong; Li, Jingyi; Yang, Feng (PLOS ONE, 2025)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by dopaminergic neuron loss and neuroinflammation, with emerging roles of peripheral immune dysregulation in disease progression. This study aimed to investigate the regulatory network of CD4 + T cells in PD through multi-omics integrative analysis. Transcriptomic and miRNA datasets from peripheral blood mononuclear cells (PBMCs) of 20 PD patients and 17 healthy controls were analyzed (GSE22491, GSE100054, GSE16658). Differential expression analysis identified 287 mRNAs and 73 miRNAs (|log₂(fold change)| ≥ 0.5, false discovery rate <0.05), with 25 immune-related mRNAs selected for further analysis. Machine learning (LASSO regression and SVM-RFE) prioritized seven hub genes, including CD4 and SEMA6A. A competing endogenous RNA (ceRNA) network was constructed, comprising 38 lncRNAs, three miRNAs (miR-155-5p, miR-27a-3p, miR-27b-3p), and their target mRNAs CD4 and SEMA6A. Four lncRNAs (including XIST, NORAD, and INE1) were identified to functionally regulate CD4. Immune cell infiltration analysis revealed increased proportions of naïve CD4 + T cells and activated dendritic cells in PD patients. CD4 expression positively correlated with γδ T cells (r = 0.48, p = 0.032) and activated NK cells (r = 0.45, p = 0.048). Gene set enrichment analysis associated CD4 with neurodegenerative pathways (e.g., Parkinson’s disease: normalized enrichment score = 1.57, p = 0.002) and oxidative phosphorylation (normalized enrichment score = 1.89, p = 7.4 × 10 ⁻ ⁶). These findings highlight a peripheral CD4 + T cell-centric ceRNA network that modulates immune-metabolic crosstalk and neuroinflammation in PD. This study provides novel insights into immune-driven neurodegeneration and suggests potential therapeutic targets for PD through metabolic-immune reprogramming.